Religiosity and substance use in U.S. adults: Findings from a large-scale national survey. (1st August 2021) - Livne, Ofir; Wengrower, Tovia; Feingold, Daniel; Shmulewitz, Dvora; Hasin, Deborah S.; Lev-Ran, Shaul
Highlights: Fewer American are attending religious services in recent decades. Past studies focusing on religiosity and substance use had numerous limitations. Using a large-scale survey, we examined associations between religiosity domains and substance use outcomes. Frequency of service attendance was independently inversely associated with substance use and SUD. Religious social support mechanisms should be used as preventive an therapeutic interventions for substance users. Abstract: Background: In recent decades, the US religious landscape has undergone considerable change such as a decline in religious service attendance. These changes may indicate that religious social support structures have deteriorated, possibly leading to a decrease in strengths of associations with substance use. Considering this, and given limitations of past studies (e.g., limited control for potential confounders), large-scale general population studies are needed to reexamine associations between religiosity domains and substance use. Methods: This cross-sectional study used data from the 2012–2013 National Epidemiologic Survey on Alcohol and Related Conditions-III (N = 36, 309). In unadjusted and adjusted models, controlling for religiosity domains and other covariates, we examined associations between three religiosity domains (importance of religiosity/spirituality, service attendance, and religious affiliation) and DSM-5 SUD. Focusing on service attendance, we also examined associations with other substance use-related outcomes. Results: Among religiosity domains, only frequency of service attendance was associated with SUD across most substances. Frequent service attendees had lower odds of alcohol use disorder (adjusted OR [aOR] = 0.4, 95 % CI 0.33, 0.51), tobacco use disorder (aOR = 0.3, 95 % CI 0.22, 0.33) and cannabis use disorder (aOR = 0.4, 95 % CI 0.24, 0.68), compared to non-service attendees. For alcohol and tobacco, the protective effect of frequent service attendance was more robust for SUD than for respective substance use. Conclusions: Despite decreasing rates of religious belief and practice in the US, service attendance independently lowered the odds of substance use and SUD across multiple substances. Results may inform religious leaders and clinicians about the value of utilizing religious social support structures in the prevention and treatment of substance use and SUD.